http://www.periodicos.rc.biblioteca.unesp.br/index.php/educacao/article/view/4856/3788 - Débora Cristina Fonseca (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
Adolescence, in a general sense, has been understood as a linear phase in human development. In this paper, we question this conception and work out the understanding of adolescence, psyche, and human development mediated by the assumptions of cultural-historical theory. For this reflection, we adopted as a reference the theoretical and interpretive framework developed from a qualitative research carried out with health professionals on the senses and meanings of adolescence. The data analysis showed the prevalence of a naturalizedview of adolescence, contributing to the invisibility of the concrete adolescent subjects in the educational practices in health care. As the National Adolescent and Youth Health Care Policy (2007) states on the need of educational and preventive practices with regard to this population, one understands the actions must be provided through a reflective process on adolescence and human development. Thus, these actions will be more effective if opportunities for reflection are created, taking into account multiple variables in the understanding of adolescence, allowing us, this way, to conceive it as a social construct rather than a natural stage in human development.